Enhanced Ohmyungsamycin A Production via Adenylation Domain Engineering and Optimization of Culture Conditions - Kim, Eunji; Du, Young Eun; Ban, Yeon Hee; Shin, Yern-Hyerk; Oh, Dong-Chan; Yoon, Yeo Joon (Frontiers in Microbiology, 2021)
Ohmyungsamycins (OMSs) A and B are cyclic depsipeptides produced by marine Streptomyces strains, which are synthesized by a non-ribosomal peptide synthetase. Notably, OMS A exhibits more potent activity against Mycobacterium tuberculosis and human cancer cells than OMS B. The substrate promiscuous adenylation (A) domain in the second module of OMS synthetase recruits either L-Val or L-Ile to synthesize OMSs A and B, respectively. Engineering of the substrate-coding residues of this A domain increased OMS A production by 1.2-fold, coupled with a drastic decrease in OMS B production. Furthermore, the culture conditions (sea salt concentration, inoculum size, and the supply of amino acids to serve as building blocks for OMS) were optimized for OMS production in the wild-type strain. Finally, cultivation of the A2-domain-engineered strain under the optimized culture conditions resulted in up to 3.8-fold increases in OMS A yields and an 8.4-fold decrease in OMS B production compared to the wild-type strain under the initial culture conditions.